Reading Comprehension Skill Using Graphic Organizer for Elementary School Students - Kurniaman, Otang; Zufriady, Zufriady; Mulyani, Eva Astuti; SB, Nugraheti Simulyasih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
Reading comprehension is a substantial skill in elementary school. If children have the skill to read, facing other lesson would be easy. This study employs a quantitative descriptive method that aims at explaining numbers in words. The result showed that the average of students' reading skill after being exposed to graphic organizer-based reading comprehension teaching materials in determining the basic thoughts was of 63.75, and students' skill in explaining information was 71.04. At this stage, their skill was considered good enough, so that an improvement to design teaching materials and trainings should be facilitated for the teachers.